Correlation between Metabolite of Prostaglandin E2 and the incidence of colorectal adenomas - Jiang, Jia; Li, Anjie; Lai, Xiaolian; Zhang, Hanqun; Wang, Chonghong; Wang, Huimin; Li, Libo; Liu, Yuncong; Xie, Lu; Yang, Can; Zhang, Cui; Lu, Shuoyan; et al. (Frontiers in Oncology, 2023)
Colorectal cancer is a common malignancy nowadays, and the incidence and mortality rate continue to rise. An important factor in the emergence of inflammation-induced colorectal carcinogenesis is elevated cyclooxygenase-2. Prostaglandin E2 overproduction is frequently equated with cyclooxygenase-2 gene overexpression. Prostaglandin E2 needs to be assessed by measuring the level of the major metabolite PGE-M in the urine. Colorectal adenoma is a precancerous lesion of colorectal cancer. We conducted research to evaluate the association between urinary levels of the prostaglandin E2 metabolite (PGE-M) and the risk of colorectal adenomas. In a population of western Chinese people, we identified 152 cases of adenoma and 152 endoscopic controls without polyps. Between the control group and the low-risk adenoma group (single adenoma with 1 cm maximum diameter and tubular/unspecified histology), there was no statistically significant change in urinary PGE-M levels. In the high-risk case group (single adenoma with a maximum diameter 1 cm and/or histology of tubular villi, villi, and any multiple adenomas), the PGE-M levels were more than 23% higher than in the control group. When compared to people with the lowest urine PGE-M levels (first quartile), people with greater urinary PGE-M levels had a higher chance of developing high-risk colorectal adenomas, with adjusted odds ratios (95% CI) of 1.65 (0.76-3.57) in the fourth quartile group, respectively (p for trend 0.013). Urinary PGE-M is associated with the risk of developing high-risk adenomas. According to our findings, urine PGE-M levels may be used to gauge the degree of colorectal adenomas risk.